ANALISIS KEUNTUNGAN USAHATANI SAYURAN SELADA HIDROPONIK PADA URBAN FARMING DI BATUKOTA KECAMATAN MALALAYANG KOTA MANADO - Herlina E. M. Abraham; Joachim Noch Karel Dumais; Caroline Betsy Diana Pakasi (AGRI-SOSIOEKONOMI, 2021)
This research aims to analyze the benefits of hydroponic lettuce farming in Urban Farming in Batu Kota, Malalayang District, Manado City. The data analysis method used in this research is quantitative analysis. Quantitative analysis used is the analysis of farming profits by calculating the difference between revenues and costs used. The data used in this study are primary data and secondary data. Primary data were obtained through observation and interviews using direct questionnaires at the hydroponic Urban Farming site through direct interviews between researchers and respondents, namely business owners. Secondary data is the collection of data and research materials obtained from ebooks, ejournals, theses and other sources. The results showed that the revenue of the Hydroponic Lettuce business was Rp. 3,200,000, while the costs incurred in the production process of lettuce for 1.5 months is Rp. 913,609.20, so that the profit on the Urban Farming business in Batu Kota, Malalayang District, Manado City is Rp. 2,286,390.80, for 1.5 months/planting period.